2016
DOI: 10.1080/15226514.2016.1183579
|View full text |Cite
|
Sign up to set email alerts
|

The role of selected tree species in industrial sewage sludge/flotation tailing management

Abstract: The aim of the study was to estimate the ability of ten tree and bush species to tolerate and accumulate Cd, Cu, Pb, Zn, and As species [As(III), As(V), and total organic arsenic] in industrial sewage sludge extremely contaminated with arsenic (almost 27.5 g kg(-1)) in a pot experiment. The premise being that it will then be possible to select the most promising tree/bush species, able to grow in the vicinity of dams where sewage sludge/flotation tailings are used as landfill. Six of the ten tested tree specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 45 publications
1
15
1
Order By: Relevance
“…However, the higher content of Pb in B. pendula stems rather than leaves described by Evangelou et al ( 2013 ) or the efficiency in As and Cd phytoextraction in leaves observed by Alagić et al ( 2013 ) were not observed in our studies. Data presented in the present manuscript support our earlier conclusion (Mleczek et al 2016 , 2017 ) that the ability of tree species to target metal phytoextraction depends not only on plant extraction ability but also on substrate characteristics.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, the higher content of Pb in B. pendula stems rather than leaves described by Evangelou et al ( 2013 ) or the efficiency in As and Cd phytoextraction in leaves observed by Alagić et al ( 2013 ) were not observed in our studies. Data presented in the present manuscript support our earlier conclusion (Mleczek et al 2016 , 2017 ) that the ability of tree species to target metal phytoextraction depends not only on plant extraction ability but also on substrate characteristics.…”
Section: Discussionsupporting
confidence: 91%
“…All seedlings were obtained from the forest nursery of the Pniewy Forest Division (52° 29′ 4″ N, 16° 15′ 28″ E). The soil where the plants were grown had the following characteristics: pH 4.6–7.4, P content 2.60–4.63 g kg −1 , K 5.57–6.62 g kg −1 , total N 0.19–0.29%, total C 2.2–3.2%, and organic matter 3.8–5.6%, depending on the tree species and the specific requirements (e.g., pH of soil) indispensable for their proper development (Mleczek et al 2016 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The key issues in decreasing the impact of mining on environmental and human health include (i) mitigation of acid mine drainage effects by preventing oxidation, neutralizing the acid, or collecting the runoff (Akcil and Koldas 2006 ) and (ii) appropriate management and disposal of tailings (Mleczek et al 2016 ). Most conventional impoundment methods involve the construction of surface ponds with raised embankments in which tailings and mine water are systematically deposited downstream, upstream, or centerline (Vick 1990 ), although methods such as sub-marine disposal or disposal of dewatered tailings as backfill are also in use (Berkun 2005 ; Fall et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…and Betula pendula Roth. were found to be the most promising for phytoextraction of As or biomass crop (Mleczek et al 2016 ). The mean biomass of the plants used in the experiment was 106.8 ± 8.6 g. A. platanoides seedlings were grown in cylindrical pots filled with unpolluted soil with pH 1M KCL = 7.3.…”
Section: Methodsmentioning
confidence: 99%